Upaya Pengembangan Profesionalisme Guru Agama Islam Untuk Meningkatkan Kualitas Belajar Siswa Di SMK Takhassus Al-Qur’an Mojotengah Wonosobo - Wigati Eka Mulyani; Ngarifin Shidiq; Ahmad Robihan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Islamic Religious Education teachers play a strategic role not only in transmitting religious knowledge but also in shaping the moral and spiritual character of students. However, challenges such as limited competence and inadequate professional development hinder the improvement of learning quality. This study aims to analyze the competence of PAI teachers and the quality of student learning, describe efforts made to develop teacher professionalism to improve learning quality, and identify supporting and inhibiting factors in these development efforts. This research used a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results showed that PAI teachers at SMK Takhassus Al-Qur’an Mojotengah had fulfilled pedagogical, professional, personality, and social competencies. The school made efforts to improve teacher professionalism through supervision, MGMP, digital-based learning innovation, and internal collaboration. Supporting factors included adequate learning infrastructure and teacher enthusiasm, while inhibiting factors included distractions from student mobile phone use and teacher administrative burdens. These findings highlight the importance of continuous training, policy reinforcement, and digital literacy to support sustainable professional development.